Ameliorative and protective effect of Bergenia ciliata (Haw.) Sternb. extract against acetaminophen-induced hepato-renal damage in rats - Makhmoor Ahmad Bhat; Rajinder Raina; Pawan Kumar Verma; Shilpa Sood; Zuhaib F. Bhat (Elsevier, 2024)
Background: Bergenia ciliata (Haw.) Sternb. is a medicinal plant bestowed with antioxidative phytochemicals and has been traditionally associated with several medicinal and health-promoting properties and used in the management of diseases.Method: The study was undertaken to determine the potential of the extract of the rhizome of Bergenia ciliata (Haw.) Sternb. at 150 and 300 mg/kg body weight (BW) to attenuate the drug-induced oxidative damage in hepatic and renal tissues of Wistar rats. The toxicity was induced by a single oral administration of acetaminophen (APAP).Results: The oral administration of APAP significantly altered the levels of hepatic and renal damage indicators in Wistar rats. The levels of superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione-s-transferase (GST) and total thiols (TTH) decreased significantly in erythrocytes, hepatic and renal tissues. Administration of B. ciliata (150 mg/kg BW) significantly decreased the elevated hepato-renal biomarkers and malondialdehyde (MDA) levels in the tissues whereas significantly increased the levels of SOD, GST and TTH in erythrocytes and liver. The higher dose of B. ciliata (300 mg/kg BW) restored the levels of plasma hepatic and renal biomarkers as well as antioxidant parameters (SOD, GST, GPx, TTH and MDA). It also reversed the histopathological alterations in hepato-renal tissues indicating the protective potential of the extract.Conclusions: Overall, the results indicated that the B. ciliata rhizome extract attenuated the drug-induced hepato-renal toxicity in a dose-dependent manner in Wistar rats and therefore, has the potential for future therapeutic uses.